GLP-1 receptor expression in human internal thoracic arteries is dependent on low-grade inflammation potentially explaining the cardiovascular protective effect of GLP1-R agonists. (3rd October 2022) - Cordeanu, E M; Qureshi, A W; Mroueh, A; Mazzucotelli, J P; Stephan, D; Schini-Kerth, V
Abstract: Background: Clinical research showed that glucagon-like peptide-1 receptor (GLP1R) agonists (GLP1RA) reduced the incidence of major cardiovascular events in diabetic patients. The protective effect was more noteworthy in patients with established cardiovascular disease, associated with chronic low-grade inflammation resulting in endothelial dysfunction and arterial remodeling and fibrosis. Despite the clinically proven cardiovascular benefit of GLP1RA, the expression pattern of GLP1R and its function in the human vasculature remain poorly studied. Aim: This study investigated the expression of GLP1R and its role in internal thoracic arteries (ITA) from patients with coronary artery disease. Methods: Human ITA were collected from patients (N=30) undergoing coronary artery bypass surgery at the University Hospital of Strasbourg. Gene expression levels were assessed using RT-qPCR, protein levels by Western blot analysis, in situ tissue localization of proteins by immunofluorescence (IF) staining, and the level of oxidative stress using dihydroethidium. Results: ITA showed a substantial difference in GLP1R mRNA levels reaching up to 7-fold among patients. GLP1R mRNA levels were positively correlated with those of SLC5A1, SLC5A2, F3, AT1R, IL1B, IL6, TNFα, VCAM1 and NCF1, and negatively with NOS3 mRNA levels. High GLP1R expressing ITA showed high levels of phosphorylated p65 NF-κB, cell adhesion molecule VCAM1, members of the angiotensin system (ACE1 and AT1R), remodeling and fibrotic markers (MMP9, MMP2, TGFβ) and a low level of eNOS, whereas the contrary was observed for low GLP1R expressing ITA. IF staining showed that GLP1R signals were predominantly observed in the endothelium of low GLP1R expressing ITA and in the vascular smooth muscle of high GLP1R expressing ITA. Prominent CD68 staining associated with the endothelium and the perivascular adipose tissue were observed in high but not low GLP1R expressing ITA. High GLP1R expressing ITA showed increased levels of oxidative stress, which were inhibited by the antioxidant N-acetylcysteine (NAC), NADPH oxidase inhibitor (VAS-2870), ACE inhibitor (perindoprilat), AT1R antagonist (losartan), TNF-α receptor neutralizing antibody (infliximab), selective SGLT2 inhibitor (empagliflozin), dual SGLT1/2 inhibitor (sotagliflozin) and by GLP1R agonists (liraglutide and semaglutide) with inhibitory effects amounting to about 50 to 75%. Conclusion: These findings indicate that GLP1R expression levels in human ITA are dependent on low-grade inflammation and linked to endothelial dysfunction, pro-thrombotic, pro-remodeling and pro-fibrotic responses. Furthermore, they were associated with increased level of oxidative stress sensitive to inhibitors of either the local angiotensin system, SGLT2, TNFα and agonists of GLP1R. Thus, the cardiovascular beneficial effects of GLP1R agonists might be attributable to their ability to reduce the pro-oxidant stimulatory signal related to low-grade inflammation. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Frency Society of Vascular Medicine (SFMV)